METHODS OF TEACHING BADMINTONIN SPORT CLASSES - Qazoqov, Sodiq Ramazonovich (The journal of contemporary issues in business and government, 2021)
This article gives you a brief overview on badminton. There is also a brief overview of the study, analysis, rules of the game, and how to use the racket during the game. There is also theoretical information about the game.